2018
DOI: 10.1002/1873-3468.13210
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of the hypothetical protein Lpg2622, a new member of the C1 family peptidases from Legionella pneumophila

Abstract: The Legionella pneumophila type II secretion system can promote bacterial growth under a wide variety of conditions and mediates the secretion of more than 25 proteins, including the uncharacterized effector Lpg2622. Here, we determined the crystal structures of apo-Lpg2622 and Lpg2622 in complex with the cysteine protease inhibitor E64. Structural analysis suggests that Lpg2622 belongs to the C1 family peptidases. Interestingly, unlike the other structurally resolved papain-like cysteine proteases, the propep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…On the other hand, NttB has putative homologues only among aquatic Piscirickettsia species and Silvanigrella aquatica . Recent structural and biochemical analysis revealed that NttB is a C1 family peptidase that diverged from common papain‐like cysteine proteases and forms a distinct phylogenetic lineage from eukaryotic cathepsins [152]. NttF has only a single homologue found in the genome of Piscirickettsia litoralis .…”
Section: Secreted Substrates (Effectors) Of the L Pneumophila T2ssmentioning
confidence: 99%
“…On the other hand, NttB has putative homologues only among aquatic Piscirickettsia species and Silvanigrella aquatica . Recent structural and biochemical analysis revealed that NttB is a C1 family peptidase that diverged from common papain‐like cysteine proteases and forms a distinct phylogenetic lineage from eukaryotic cathepsins [152]. NttF has only a single homologue found in the genome of Piscirickettsia litoralis .…”
Section: Secreted Substrates (Effectors) Of the L Pneumophila T2ssmentioning
confidence: 99%
“…However, the nature of this motif and how it is sampled by different type II secretion systems remains unclear. In L. pneumophila, the T2SS exports an unusually large number of substrates and with contributions from this study this represents the largest catalog of intact and subdomain substrate structures from any one T2SS; namely LapA, LapB, Map, NttA, NttB, NttC, NttD, NttE, NttG, and the ChiA C-terminal chitinase/mucinase domain (Dhatwalia et al, 2015;Zhang et al, 2017a,b;Gong et al, 2018;White et al, 2018;Chen et al, 2020;Rehman et al, 2020). Furthermore, the L. pneumophila T2SS appears to transport two of the smallest substrates that have identified to date, NttA and NttC (11.5 kDa each), although association of a co-factor with NttC could promote its oligomerization.…”
Section: Discussionmentioning
confidence: 86%
“…3A-B) (Gong et al ., 2018). Lpg2586 also possesses an N-terminal β-sheet that was shown to be involved in regulating the activity of Lpg2622 (Gong et al ., 2018). Our analysis also suggested that residues Cys106, His291, Asn320, and Gln100 in Lpg2586 may be important for catalysis based on the role of equivalent residues demonstrated for Lpg2622 (Appendix Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Lpg2586, also identified as a T4SS effector containing a potential cysteine protease domain, shares high sequence similarity (∼30%) with the L. pneumophila effector Lpg2622. The latter effector has been associated with the type II secretion system (T2SS) of this bacterium and was characterized as a member of the C1 peptidase family (Gong et al , 2018). Along with the experimentally defined structure of Lpg2622 (PDB 6A0N), the model of Lpg2586 also contains a unique hairpin-turn-helix motif, which was shown to be essential for Lpg2622 protease activity (Appendix Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation